P270 Development Of Quality Indicators Of Low Risk Labor Provided Primarily By Midwives: Based On Clinical Practice Guidelines With A Modified Delphi Method. (15th August 2013) - Ueda, K; Ohtera, S; Misato, K; Nakayama, T
Abstract : Background: In Japan some labour units have started services for low risk labour provided primarily by midwives with the assistance of obstetricians. However, real practices varied with facilities and quality of care has not been sufficiently assured. Objectives: We aimed to develop quality indicators of low-risk labour provided primarily by midwives in Japan. Methods: We systematically searched databases to select related indicators and clinical practice guidelines. Using a modified Delphi method, a multidisciplinary panel including two women who experienced labour and were not health professionals was assembled and a meeting was held. After the panel members rated the candidates individually, consensus was attained for each indicator. Results: An electronic search retrieved 104 guidelines (2043 key recommendations) from which 32 guidelines (166 key recommendations) were selected. Some recommendations were excluded due to difficulties in measuring and others due to evidence against following certain guidelines. Additionally, 31 existing quality indicators were identified. The panel discussed 25 candidate indicators: 18 indicators were adopted, six indicators were not adopted, one indicator was modified. Four indicators were added later following discussion. Consequently, 23 quality indicators of care were chosen. Discussion: A pilot test of these indicators at multiple facilities should contribute to future development of guideline-based quality indicators. Implications for Guideline Developers/Users: Guideline developers should be more conscious in making recommendations that are potentially used as quality indicators.